America's rusted families: working-class political participation through three biological generations (1965–1997). Issue 6 (19th September 2022) - Jeannet, Anne-Marie
Abstract: Has social reproduction through families preserved unequal political participation amongst the working class in post-industrial society? This article builds on both political and sociological traditions to consider the family as a tenacious social structure that reproduces political participation from one generation to the next. In order to answer this empirically, the study uses a longitudinal panel data of political behaviour across three biological generations in the United States (1965–1997). The findings show that respondents who grew up in working-class families are less likely to vote as adults regardless of whether they have working-class occupations or not. The transmission of un-equal participation is partially mediated by the voting behaviour of the parent who models this behaviour to their children. The study also shows that the second generation of respondents transmits low political participation to their offspring in the third generation. This study implies that occupational structures of a past industrial society are still politically relevant and that inequalities in political participation remain a legacy amongst the biological descendants of working-class families from the 1960s. Supplemental data for this article can be accessed online at: https://doi.org/10.1080/01402382.2022.2044220 .